Peningkatan Kesejahteraan Subjektif (Subjective Well-Being) melalui Intervensi Psikologi Positif Berbasis Kelompok untuk Meningkatkan Positive Affect Remaja di Lingkungan Perumahan - Annisa Dwi Nastiti; Dean Algustav Nurhadi; Salwa Azzahra Julianti; Sary Haswinda Nasution; Tiyas Dwi Cahya (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
Subjective well-being is an important foundation in adolescent development, particularly for adolescents living in residential neighborhoods who face academic pressure, peer pressure, and uncertainty regarding their educational or economic future. This study aims to determine the effectiveness of a group-based positive psychology intervention in increasing positive affect as one component of subjective well-being among adolescents aged 15–19 years living in a residential neighborhood. The intervention was carried out with eight adolescents through four sessions designed using psychoeducation, ice breaking, group discussion, and structured positive psychology exercises, namely gratitude journal, strengths mapping, gratitude letter, and positive vision board. Data were collected through observation during the activities and pre-test and post-test measurements using the Scale of Positive and Negative Experience (SPANE). Descriptive analysis showed that the mean positive affect score increased from 27 to 32, while the mean negative affect score decreased from 20 to 13 after the program. These findings indicate that a group-based positive psychology intervention emphasizing emotional awareness, strengths exploration, expression of gratitude, and future aspiration setting is effective in increasing positive affect among adolescents in residential neighborhoods and can serve as an alternative program for developing adolescents' psychological well-being.